Implementation of Internet of Things in a Smart Trash Bin System for Organic and Inorganic Waste Sorting using Solar Cells at SMP Al Wathoniyah 9 Jakarta - Dwi Prasetyo; Suzuki Syofian (Journal TIFDA (Technology Information and Data Analytic), 2025)
Ineffective waste management in schools, characterized by unsegregated waste collection, hinders recycling efforts and harms the local environment. This study addresses this issue by designing, implementing, and evaluating an Internet of Things (IoT)-based smart trash bin system with automatic organic and inorganic waste sorting, powered by solar energy for operation at SMP Al Wathoniyah 9 Jakarta. The system utilizes an ESP32 microcontroller with a multi-sensor detection logic: an inductive proximity sensor for metals, a capacitive proximity sensor for plastics, and an infrared sensor for organic waste, complemented by ultrasonic sensors for fill-level monitoring. Deployed and tested in the school environment, the system demonstrated high reliability, achieving a sorting accuracy of 96.67% across 2,598 trials. Data on waste volume and type are transmitted and displayed in real-time via a dedicated web-based monitoring dashboard. The results confirm the system's effectiveness as a practical tool for automated waste segregation. Furthermore, its solar-powered operation ensures energy independence, while the real-time monitoring capability supports smarter waste management. This implementation serves as a concrete model for integrating environmental technology into education, promoting sustainability awareness and supporting the development of smart schools